Effect of Chemical Fertilizer and Spraying with Nano Fertilizer on Characteristics of cauliflower Brassica Oleracea Var botrytis - Abdul Rahman, Lubna Sabah; Angel, Sabeeh Abdul Wahab; Badr, Basim Rahim (Journal of agricultural, environmental and veterinary sciences, 2018)
The field experiment was conducted during the autumn planting season 2017- 2018 In the Research Department of Horticulture and Garden Engineering- Faculty of Agriculture، University of Diyala The experience included 12 Treatment resulting from combinations among the four levels of chemical fertilizer are 0(Without adding fertilizer)، and add 1/3 of the recommended quantity and Add 2/3 of the recommended quantity and 1 add the recommended amount of chemical It has its symbol (T0، T1، T2، T3) Respectively And three levels of nano fertilizer(nano zinc oxide) Research aims To determine the best level of chemical fertilizer and nano fertilizer And determine the optimum level for them to improve the growth of cauliflower، The results showed that the addition of chemical fertilizers in the recommended quantity led to a significant increase in head dimeter 21.73 cm and Total plant weight 3.99 Kg plant- 1 and total yield 133.99 ton H- 1 and Crud weights 2.09 and total yield crud 69.56 ton H- 1 The results also showed that spraying the nano fertilizer of 50 mg per liter- 1led to a significant head dimeter 21.25cm and Total plant weight 4.07 Kg plant- 1 and total yield 135.75ton H- 1 and Crud weights 1.76 and total yield crud 58.75 ton H- 1